Eucalypts of Hodogaya: Organic cultural diplomacy at Yokohama War Cemetery - Tsakonas, Athanasios; Pieris, Anoma (Interstices: Journal of Architecture and Related Arts, 2023)
Located within a former Hodogaya recreation park about 5 kilometres west of the city centre, the 27-acre Yokohama War Cemetery is the primary commemoration and remembrance site for Commonwealth Allies of the Second World War within mainland Japan. Alongside Hiroshima Peace Park and Tokyo’s Yasakuni Shrine, it serves to remind both foreign nationals and locals of war’s consequences. Yet beyond official narratives, its establishment in the peripheral city of Yokohama, rather than Tokyo, Japan’s imperial, cultural, and political heart remains relatively unknown. This paper aims to understand better Australia’s significant role in this war cemetery’s creation. Under the auspices of the Australian War Graves Service, Australian and Japanese designers and the contractors of both nations collaborated to create a significant setting for deceased servicemen and women. Whilst ostensibly another of the Commonwealth War Graves Commission’s many such sites worldwide, Australian involvement offers an alternative interpretation of its conception. By examining the factors leading to the considered allocation of the site and its subsequent layout design, this study intends to enhance our knowledge of this important Australian contribution to our region—by asking why this war cemetery differs considerably from the orthodox nature of the conventional war cemeteries; by unveiling the many unknown architects, landscapers, contractors, and officials that put aside differences to collaborate on this war cemetery and its memorials; and by recording and analysing the careful detailing and construction of the memorials using local and imported materials. The lens from architectural history offers unique insights into these processes.